2014
DOI: 10.1103/physrevb.89.115312
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic excited-state Mn2+dimers in Zn1xMnxSe quantum dots observed by time-resolved magnetophotoluminescence

Abstract: Colloidal Mn 2+ -doped semiconductor nanocrystals are solution processable analogs of classic phosphor and diluted magnetic semiconductor materials with promising applications ranging from fluorescence microscopy to spintronic information processing. At doping levels of only a few cation mole percent, Mn 2+ dimers form in appreciable concentration and cause shortened photoluminescence decay times and reduced luminescence circular polarization under applied magnetic fields. Here, we show that these differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 55 publications
(70 reference statements)
4
60
0
Order By: Relevance
“…This technique has shown very promising results in our lab for the theoretical characterization of the excited states in doped semi-conductor quantum dots. 28,[41][42][43][44][45][46] Using this technique on a broad range of NV-diamond QD sizes, we explore quantum confinement effects on the highly localized mid-gap transitions, as well as the higher energy CT states. Because CT transitions are broad and show strong spectral overlap with many other optical features, this theoretical method is strongly motivated by the desire to disentangle the full range of electronic transitions in NV-doped nanodiamond.…”
Section: -40mentioning
confidence: 99%
“…This technique has shown very promising results in our lab for the theoretical characterization of the excited states in doped semi-conductor quantum dots. 28,[41][42][43][44][45][46] Using this technique on a broad range of NV-diamond QD sizes, we explore quantum confinement effects on the highly localized mid-gap transitions, as well as the higher energy CT states. Because CT transitions are broad and show strong spectral overlap with many other optical features, this theoretical method is strongly motivated by the desire to disentangle the full range of electronic transitions in NV-doped nanodiamond.…”
Section: -40mentioning
confidence: 99%
“…The small τ 1 and A 2 for 0.025mmol-Mn:AIZS/ZnS NCs could be related to the low Mn level in the hosts. Interestingly, according to the literature [3334], a lower Mn level in host NCs should produce a longer PL lifetime probably because the Mn-Mn distance is long. Such a conflict indicates that the Mn emission with Mn-Mn coupling could be existing but not be the major PL mechanism for the fast decay (corresponding to τ 1 ) in Mn:AIZS/ZnS NCs.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that the lifetimes in the range of tens of microseconds may result from radiative decay through trap states or be related to the emission of Mn dopants (diffused from MnS surface to ZnS shell) with enhanced overlap between 3d and sp host states caused by lattice strain due to the spatial distribution of Mn dopants in host NCs. Other authors reported that the spatial distribution of Mn in ZnSe or ZnS NCs affects the PL decay significantly [3334]. Homogenous Mn dopants in ZnSe or ZnS NCs result in single exponential decay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations